Transhuman Reproduction: A Comparative Analysis between Natura, by Iolanda Zúñiga, and The Growing Season, by Helen Sedgwick - Alonso Alonso, María (Madrygal. Revista de Estudios Gallegos, 2026)
This article offers a comparative approach to the novels Natura, by Galician author Iolanda Zúñiga, and The Growing Season, by British author Helen Sedgwick, to analyse the critical interpretation that both authors make of the use of artificial wombs in future societies. To this end, transhumanism is used as a theoretical framework, a philosophy which postulates the need to take advantage of current scientific and technological advances to create bio-enhanced beings. In the works, reproductive sexuality is replaced by in-vitro reproduction and artificial wombs, which, far from liberating women from the dangers of natural pregnancies and births, represent a further step in their oppression and repression. In this way, both Zúñiga and Sedgwick contradict one of the main arguments of second-wave American feminism, such as the ones postulated by Firestone and Pateman, which suggested that the confiscation of women’s reproductive sexuality through the use of artificial wombs would end patriarchy and, therefore, free them from any type of oppressive system. The result of this comparative analysis indicates that both Natura and The Growing Season, despite being works written in two different languages and belonging to two distinct literary traditions, have in common the bioconservatist reading they make of any type of Manichean use of scientific and technological advances due to their potential for both patriarchal and capitalist